The Challenge of Indonesian Diplomacy Against Palm Oil Discrimination - Windratmo Suwarno (Jurnal Ilmiah Hubungan Internasional, 2019)
ABSTRACTIndonesia will continue to face a discrimination of palm commodity in European Union in the next decade. The challenge the European black campaign against palm oil is not easy to overcome. Most of European people have a bad perception about palm oil. The issue of palm oil is not only about the forestation, but also it is influenced by bad perception on health and social impact. It is a time for Indonesian diplomacy to make a strategy to resolve this issue by improving public diplomacy through lobbying, corporate diplomacy and identification of stakeholders. Although in the European Parliament statement does not mention the elimination of palm oil, discrimination against palm oil will continue in the trilogy. Palm oil must face accusations from various interested parties such as NGOs and members of parliament who have relations with farmers in Europe. They have a strategy to phase out using palm oil for biofuels. The issue of palm oil is not only about a battle of the vegetable industry anymore, but it is more about politics to defend other vegetable oil in the market by disseminating any kind issues related to oil palm plantation. It must be deal with the total diplomacy taken by all stakeholders in Indonesia and in Europe.           Key words: oil palm, public diplomacy, biofuels, European Parliament